The inotropic peptide βARKct improves βAR responsiveness in normal and failing cardiomyocytes through Gβγ-mediated L-type calcium current disinhibition - Völkers, Mirko; Weidenhammer, Christian; Herzog, Nicole; Qiu, Gang; Spaich, Kristin; von Wegner, Frederic; Peppel, Karsten; Müller, Oliver J.; Schinkel, Stefanie; Rabinowitz, Joseph E.; Hippe, Hans-Jörg; Brinks, Henriette; et al. (Circulation research, 2011)
Rationale: - - The Gβγ-sequestering peptide β-adrenergic receptor kinase (βARK)ct derived from the G-protein-coupled receptor kinase (GRK)2 carboxyl terminus has emerged as a promising target for gene-based heart failure therapy. Enhanced downstream cAMP signaling has been proposed as the underlying mechanism for increased β-adrenergic receptor (βAR) responsiveness. However, molecular targets mediating improved cardiac contractile performance by βARKct and its impact on Gβγ-mediated signaling have yet to be fully elucidated. - - Objective: - - We sought to identify Gβγ-regulated targets and signaling mechanisms conveying βARKct-mediated enhanced βAR responsiveness in normal (NC) and failing (FC) adult rat ventricular cardiomyocytes. - - Methods and Results: - - Assessing viral-based βARKct gene delivery with electrophysiological techniques, analysis of contractile performance, subcellular Ca2+ handling, and site-specific protein phosphorylation, we demonstrate that βARKct enhances the cardiac L-type Ca2+ channel (LCC) current (ICa) both in NCs and FCs on βAR stimulation. Mechanistically, βARKct augments ICa by preventing enhanced inhibitory interaction between the α1-LCC subunit (Cav1.2α) and liberated Gβγ subunits downstream of activated βARs. Despite improved βAR contractile responsiveness, βARKct neither increased nor restored cAMP-dependent protein kinase (PKA) and calmodulin-dependent kinase II signaling including unchanged protein kinase (PK)Cε, extracellular signal-regulated kinase (ERK)1/2, Akt, ERK5, and p38 activation both in NCs and FCs. Accordingly, although βARKct significantly increases ICa and Ca2+ transients, being susceptible to suppression by recombinant Gβγ protein and use-dependent LCC blocker, βARKct-expressing cardiomyocytes exhibit equal basal and βAR-stimulated sarcoplasmic reticulum Ca2+ load, spontaneous diastolic Ca2+ leakage, and survival rates and were less susceptible to field-stimulated Ca2+ waves compared with controls. - - Conclusion: - - Our study identifies a Gβγ-dependent signaling pathway attenuating cardiomyocyte ICa on βAR as molecular target for the Gβγ-sequestering peptide βARKct. Targeted interruption of this inhibitory signaling pathway by βARKct confers improved βAR contractile responsiveness through increased ICa without enhancing regular or restoring abnormal cAMP-signaling. βARKct-mediated improvement of ICa rendered cardiomyocytes neither susceptible to βAR-induced damage nor arrhythmogenic sarcoplasmic reticulum Ca2+ leakage.